Pricing Damaged Goods - R. Preston McAfee (Kiel Institute for the World Economy (IfW), 2007)
Companies with market power occasionally engage in intentional quality reduction of a portion of their output as a means of offering two qualities of goods for the purpose of price discrimination, even absent a cost saving. This paper provides an exact characterization in terms of marginal revenues of when such a strategy is profitable, which, remarkably, does not depend on the distribution of customer valuations, but only on the value of the damaged product relative to the undamaged product. In particular, when the damaged product provides a constant proportion of the value of the full product, selling a damaged good is unprofitable. One quality reduction produces higher profits than another if the former has higher marginal revenue than the latter.
Keywords: L15; D43; 330